Alfa fetoproteína e desenvolvimento embrionário - Mello, Romário de Araújo (Bioikos – Título não-corrente, 1990)
Alfafetoprotein (AFP) is a major serum glycoprotein during embryonic and early postnatal life. A number of diverse biologic functions have been attributed to AFP, including osmotic and carrier function and immunosuppresive activity.